Preventive benefit of access to fluoridated water for young adults. (13th February 2017) - Spencer, A. John; Liu, Pingzhou; Armfield, Jason Mathew; Do, Loc Giang
Abstract: Water fluoridation has been repeatedly associated with lower caries experience in children but uncertainty still exists on strength and extent of the association into adulthood. Objective: To analyze the preventive effect of access to fluoridated water on dental caries among young adults. Methods: In 1991/92 a cross‐section of South Australian children aged 5‐17 were recruited. Parents provided information on residential history, socioeconomic status, and behaviors. Children were dentally examined. Across 2006/2011, these participants were traced and recruited to follow‐up examination. Similar data were updated. Residential history was used to compute percent lifetime access to fluoridated water (%LAFW). The participants underwent examinations scoring tooth surfaces decayed, missing and filled due to caries (DMFS). Unadjusted and adjusted models were generated using generalized linear modeling to estimate rate ratios (RR). Results: Half of the 1991/92 participants traced could be recruited ( n = 1, 221) aged 20‐35 years. Mean DMFS was 5.57 (95 percent CI: 5.0‐6.1). Adjusted RR of DMFS for %LAFW (Birth‐2006) 0‐75 percent against 100 percent was 1.26 (1.01‐1.57). RRs for 0‐75 percent against 100 percent of %LAFW (1991‐2006) and %LAFW (Birth‐2006) were higher than that for %LAFW (Birth‐1991). However, these differences were small once the comparisons were adjusted for all covariates. Conclusion: Early life access to fluoridated water was not as strongly associated with caries outcomes than either full lifetime access or access across the more proximal years with the caries outcome of young adults, especially after adjustment for covariates which may become increasingly important across longer spans of the life course.